Can We Call the Speech Acts of Heroes who Bounce Back from Defeat Ultimatives? - Purnomo, SF Luthfie Arguby (Universitas Sanata Dharma, 2024)
In animated films and video games, there is always a scene where the heroes bounce back from defeat and charge the villains with a final strike. I argue that this particular scene has a specific speech act – ultimative. To prove this claim, I employed apostrophe as a dramatic device by Wagener (1931), speech act markers by Zeevat (2003), speech act formula by Pawley (2009), and invocation by Frankfurter (2019) on twenty titles of animated films and video games to indicate the presence of ultimatives. The findings indicate that ultimatives have distinctive traits. Speech act markers of sudden changes of speech and narratives, pathic speech act markers, and speech act markers of invocation construct them. The combination of these three elements constructs the speech act of ultimatives. I also found that ultimatives in animated films and video games have different functions due to different characteristics and features of the media. In animated films, ultimatives function as a narrative marker indicating that ultimatives signify the plot progression and rationalization. In video games, ultimatives function not only as a narrative marker but also as mechanical marker. Functioning as a mechanical marker indicates that ultimatives require the players to perform certain mechanical interactions through button configuration to bounce back from possible game over. Narrative designers of both animated films and video games could employ the results of this study as a consideration in designing dramatic battle scenes that contain apostrophes to evoke narrative engagement from the audiences and gamers.